DB2 administration exam guide - Sanders, Roger E. (McGraw-Hill, 2002)
This authoritative reference offers complete coverage of all material on the three DB2 exams. You'll find exam objectives at the beginning of each chapter, helpful exam tips, end-of-chapter practice questions, and photographs and illustrations. The bonus CD-ROM contains practice tests, and hundreds of questions. This comprehensive guide will not only help you pass the certification exams, but will also serve as an invaluable on-the-job reference